The role of state aid control in improving bank resolution in Europe - Mathias Dewatripont; Gregory Nguyen; Peter Praet; André Sapir (Bruegel, 2010)
The financial crisis exposed Europe's inadequacy in developing an effective banking resolution framework that could bring together national authorities and set guidelines for their coordination. The European Commission, through its assessment of state aid cases, managed to avoid single market distortions and mitigate moral hazard. This Policy Contribution explains why in the long-term Europe needs a single resolution authority. The authors Bruegel Senior Research Fellow André Sapir, Mathias Dewatripont, ULB and CEPR; Gregory Nguyen, National Bank of Belgium, and Peter Praet, National Bank of Belgium, show how in the short-term, the European Commission, through its state aid control discipline, can set the foundation for a new crisis resolution architecture. It can act as a substitute to improve coordination among member states and complement a European resolution authority once it is set up.
Keywords: 330; Bankenpolitik; Bankenaufsicht; Bankenkrise; EU-Staaten